Tim O'Reilly and Web 2.0: The economics of memetic liberty and control - Allen, Matthew (Informit / RMIT University, School of Media and Communication, 2009)
This paper presents an account of the role of Tim O'Reilly, both as an individual and as a corporate entity (O'Reilly Group), in the creation, spread and use of the concept of Web 2.0. It demonstrates that, whatever Web 2.0's current uses to describe variously the technologies, politics, commerce or social meaning of the Internet, it originates as a deliberately open signifier of novel and potential Internet development in the mid-2000s. The paper argues that O'Reilly has promoted the diversity of the term's meanings and uses - celebrating textual liberties - but has also emphasised the special role that O'Reilly plays in providing the authoritative definition of that term. In essence, O'Reilly profits from this 'control' of the idea of Web 2.0 but that, to enjoy that control O'Reilly must also allow differences in meaning. The paper concludes by suggesting that Web 2.0 therefore signifies a new kind of economics that brings together freedom and control in a new way.